Safety, Immunogenicity, Efficacy and Effectiveness of Inactivated Influenza Vaccines in Healthy Pregnant Women and Children Under 5 Years: An Evidence-Based Clinical Review - Bansal, Amit; Trieu, Mai-Chi; Mohn, Kristin G. I.; Cox, Rebecca Jane (Frontiers in Immunology, 2021)
Annual influenza vaccination is often recommended for pregnant women and young children to reduce the risk of severe influenza. However, most studies investigating the safety, immunogenicity and efficacy or effectiveness of influenza vaccines are conducted in healthy adults. In this evidence-based clinical review, we provide an update on the safety profile, immunogenicity, and efficacy/effectiveness of inactivated influenza vaccines (IIV) in healthy pregnant women and children <5 years old. Six electronic databases were searched until 27th May 2021. We identified 3731 articles of which 93 met eligibility criteria and were included. The IIV were generally well tolerated in pregnant women and young children with low frequencies of adverse events following IIV administration, however, continuous vaccine safety monitoring systems are necessary to detect rare adverse events. IIV generated good antibody responses and the seroprotection rates after IIV were moderate to high in pregnant women (ranged 65-96%) and young children (ranged 50-100%) varying between different influenza types/subtypes and seasons. Studies show vaccine efficacy/effectiveness of 50-70% in pregnant women and 20-90% in young children against lab-confirmed influenza, although the efficacy/effectiveness depended on the study design, host factors, vaccine type, manufacturing practices, and the antigenic match/mismatch between the influenza vaccine strains and the circulating strains. Current evidence suggests that the benefit of IIV far outweighed the potential risks and IIV should be recommended for pregnant women and young children.